Pengembangan Buku Ajar Bahasa Arab Berbasis Muhadatsah untuk Maharah Kalam Siswa Kelas X Madrasah Aliyah: PengeDevelopment of Arabic Language Textbooks Based on Muhadatsah for Maharah Kalam of Grade X Students of Madrasah Aliyahmbangan Buku Ajar Bahasa Arab Berbasis Muhadatsah untuk Maharah Kalam Siswa Kelas X Madrasah Aliyah - Lastry Retnasary; Nurul Hidayah; Amrini Shofiyani (Information Technology and Science (ITScience), 2026)
This research is motivated by the low mastery of Arabic speaking skills of students at MA Al-Ihsan Kalijaring Jombang, which has an impact on decreasing student interest and learning outcomes. This condition occurs because the learning process is still conventional, so that students tend to be passive and easily feel bored in following Arabic language learning. Therefore, this research aims to develop a Muhadatsah-based Arabic language textbook as a solution to overcome the low mastery of Arabic speaking skills of students. The method used in this research is Research and Development (R&D) by adopting the ADDIE model. The subjects of this research were 20 students of class X IPA and IPS MA Al-Ihsan Kalijaring Jombang. The data collection instruments used included questionnaires and tests. The types of data analyzed produced qualitative and quantitative data, which showed that: (1) teaching materials have been successfully developed in the form of Muhadatsah-based Arabic language textbooks; (2) based on the validity test, the developed textbooks reached a valid feasibility level with an average of 79.33% from material experts and 78.33% from media experts; and (3) the level of effectiveness of the textbook is classified as very effective, which is shown by comparing the pre-test scores with an average of 30% and the post-test with an average of 90%.